On the "odoresque" and "aero-perfumes" - Verbeek, Caro (Amfiteater (Ljubljana), 2021)
For her doctoral dissertation “In Search of Lost Scents,” art and scent historian Caro Verbeek (Vrije Universiteit Amsterdam, Kunstmuseum, The Hague) collected olfactory neologisms or newly invented smell related words from (art) historical sources ranging from 1855 to 1975, which she categorised according to the themes poetry, mind, concepts, material and synaesthesia. Three never-before-published artistic illustrations by the author help establish a more embodied cognition of the meaning of some of these concepts, as including “smell images” is impossible. In addition, she has created a “synaesthetic odour wheel” based on literary sources (2021).
Keywords: futurism; futurizem; krog vonjav; neologisms; neologizem; olfaction; parfum; perfume; scent wheel; simbolizem; sinestezija; symbolism; synaesthesia; vocabulary; vonj